CoMo sulfide-catalyzed hydrodeoxygenation of lignin model compounds: An extended reaction network for the conversion of monomeric and dimeric substrates - Jongerius, Anna L.; Jastrzebski, Robin; Bruijnincx, Pieter C.A.; Weckhuysen, Bert M. (Journal of catalysis, 2012)
Extensive hydrodeoxygenation studies with a sulfided CoMo/Al2O3 catalyst were performed on a library of lignin model compounds. An extended reaction network is proposed, showing that HDO, demethylation, and hydrogenation reactions take place simultaneously. [Display omitted] . ► Extensive study of aromatic oxygenates allowed elucidation of the HDO reaction pathway. ► Hydrodeoxygenation competes with O-demethylation, hydrogenation, and ring methylation. ► CoMo-catalyzed HDO of a library of substrates results nonetheless mainly in phenolics production. ► Abundant lignin–ether linkages are readily cleaved under HDO conditions. In the present work, extensive hydrodeoxygenation (HDO) studies with a commercial sulfided CoMo/Al2O3 catalyst were performed on a library of lignin model compounds at 50bar hydrogen pressure and 300°C in dodecane, using a batch autoclave system. The catalyst was activated under hydrogen atmosphere prior to the reaction, and the spent catalyst was analyzed using thermogravimetric analysis. An extended reaction network is proposed, showing that HDO, demethylation, and hydrogenation reactions take place simultaneously. HDO of mono-oxygenated substrates proved to be difficult at the applied conditions. Starting from most positions in the network, phenol, and cresols are therefore the main final products, suggesting the possibility of convergence on a limited number of products from a mixture of substrates. HDO of dimeric model compounds mimicking typical lignin linkages revealed that coumaran alkyl ethers and β-O-4 bonds can be broken, but 5–5′ linkages not.